Contribution of sorption, DOC transport and microbial interactions to the 14C age of a soil organic carbon profile: Insights from a calibrated process model. (September 2015) - Ahrens, Bernhard; Braakhekke, Maarten C.; Guggenberger, Georg; Schrumpf, Marion; Reichstein, Markus
Abstract: Profiles of soil organic carbon (SOC) are often characterized by a steep increase of 14 C age with depth, often leading to subsoil 14 C ages of more than 1000 years. These observations have generally been reproduced in SOC models by introducing a SOC pool that decomposes on the time-scale of millennia. The overemphasis of chemical recalcitrance as the major factor for the persistence of SOC was able to provide a mechanistic justification for these very low decomposition rates. The emerging view on SOC persistence, however, stresses that apart from molecular structure a multitude of mechanisms can lead to the long-term persistence of organic carbon in soils. These mechanisms, however, have not been incorporated into most models. Consequently, we developed the SOC profile model COMISSION which simulates vertically resolved SOC concentrations based on representations of microbial interactions, sorption to minerals, and vertical transport. We calibrated COMISSION using published concentrations of SOC, microbial biomass and mineral-associated OC (MOC), and in addition, 14 C contents of SOC and MOC of a Haplic Podzol profile in North-Eastern Bavaria, Germany. In order to elucidate the contribution of the implemented processes to the 14 C age in different parts of the profile, we performed model-experiments in which we switched off the limitation of SOC decomposition by microbes, sorptive stabilization on soil minerals, and dissolved OC (DOC) transport. By splitting all model pools into directly litter-derived carbon and microbe-derived organic carbon, we investigated the contribution of repeated microbial recycling to 14 C ages throughout the profile. The model-experiments for this site lead to the following implications: Without rejuvenation by DOC transport, SOC in the subsoil would be on average 1700 14 C years older. Across the profile, SOC from microbial recycling is on average 1400 14 C years older than litter-derived SOC. Without microbial limitation of depolymerization, SOC in the subsoil would be on average 610 14 C years younger. Sorptive stabilization is responsible for relatively high 14 C ages in the topsoil. The model-experiments further indicate that the high SOC concentrations in the Bh horizon are caused by the interplay between sorptive stabilization and microbial dynamics. Overall, the model-experiments demonstrate that the high 14 C ages are not solely caused by slow turnover of a single pool, but that the increase of 14 C ages along a soil profile up to ages >1000 years is the result of different mechanisms contributing to the overall persistence of SOC. The dominant reasons for the persistence of SOC are stabilization processes, followed by repeated microbial processing of SOC. Graphical abstract: Highlights: A SOC profile model was developed and calibrated to explain 14 C ages >1000 years of subsoil OC. Factorial model-experiments revealed processes explaining the persistence of SOC. 14 C ages could be explained without introducing a SOC pool with a millennial turnover time. Sorptive stabilization is the dominant process for modeled topsoil 14 C ages. Energy limitation, microbial recycling and sorption govern modeled subsoil 14 C ages.